Variability of Drosophila melanogaster radius incompletus trait expressivity under the food fortification by folate-methionine cycle metabolites - Волкова, Н. Є.; Філіпоненко, Н. С.; Воробйова, Л. І. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The aim of study was to determine how the excess of certain (key) metabolites of folate-methionine cycle (folic acid, methionine, betaine) in the diet affects Drosophila melanogaster radius incompletus trait expressivity. Folate metabolism is a supplier of one-carbon chemical groups to the number of vital cell processes (purine nucleotides biosynthesis, methionine regeneration, DNA, RNA and proteins methylation) and, therefore, it is directly related to the gene activity regulation. This prompted the supplements choice for study. For the experiment we used D. melanogaster stock with radius incompletus (ri) gene mutation. The expressivity of radius incompletus trait appeared to be a convenient model with well-studied genetic control to evaluate the effect of various factors. It has been established that an excess of folic acid, betaine or methionine in culture medium affects D. melanogaster radius incompletus trait expressivity. The direction and strength of effect depend on the sex of individual developed in the medium with one of mentioned supplements. Females appeared to be more sensitive. Each of the dietary supplements used was characterized by a specific effect on studied trait expressivity: under betaine influence we observed a significant decrease in the trait expression in females but not in males; under folic acid action sex-specific differences stayed stable; development in the medium with methionine excess resulted in a decrease of the studied index mean values with an increase of the individuals’ variability. Evaluation in terms of fluctuating asymmetry proved more stable development of males in changing conditions, as compared to females.